The causal relationship between risk of developing bronchial asthma and frailty: a bidirectional two-sample Mendelian randomization study - Ma, Xiao; Xu, Haoran; Xie, Jinghui; Zhang, Lu; Shi, Mengyao; Li, Zegeng (Frontiers in Medicine, 2023)
Background A potential link between asthma and frailty has been suggested in previous studies. However, the nature of the causal relationship between these two conditions warrants further investigation. Therefore, this study assessed the bidirectional causality between asthma and frailty risk using two-sample Mendelian randomization (MR). Methods The study data were obtained from the genome-wide association study (GWAS) dataset, with 337,159 samples representing asthma data and 175,226 samples representing frailty. The causal relationship between the two disorders was assessed by selecting the single nucleotide polymorphisms (SNPs), significantly associated with both asthma and frailty. The inverse variance weighting (IVW) method was used as the main analytical method to estimate the possible influence of causality. Sensitivity analysis was also performed using Mr-Egger intercept, funnel plot, “leave-one-out,” and Cochran Q test. In addition, potential mediators were investigated by risk factor analysis. Result The IVW method showed an increased risk of frailty due to increased genetic susceptibility factors and the number of to asthma (OR = 2.325, 95%CI:1.958–2.761; p = 6.527498e-22), while no horizontal pleiotropy was observed for the Mr-Egger intercept (p = 0.609) and the funnel plot. The Cochran Q value was 72.858, p = 0.024, and there was heterogeneity in the Cochran Q-value. No single SNP was observed for “leave-one-out” that had a biasing effect on the instrumental variables. In addition, genetic susceptibility to frailty was associated with asthma (OR = 1.088, 95%CI:1.058–1.119; p = 4.815589e-09). In the causal relationship described above, several risk factors for frailty are complex, with asthma leading to a significant reduction in physical activity endurance. Conclusion Our findings suggest a probable positive causal effect of asthma on the risk of developing frailty, potentially mediated by reduced physical activity endurance. At the same time, a causal relationship exists between frailty and asthma. Therefore, assessment strategies for frailty should include asthma and vice versa.